2018
DOI: 10.1053/j.gastro.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline on Screening for Colorectal Cancer in Individuals With a Family History of Nonhereditary Colorectal Cancer or Adenoma: The Canadian Association of Gastroenterology Banff Consensus

Abstract: The increased risk of CRC associated with an FH of CRC or advanced adenoma warrants more intense screening for CRC. Well-designed prospective studies are needed in order to make definitive evidence-based recommendations about the age to commence screening and appropriate interval between screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 109 publications
(186 reference statements)
0
84
0
7
Order By: Relevance
“…We did not address the presence of having a FH of adenomas despite current surveillance recommendations according to different clinical practice guidelines. [5][6][7] Imperiale and Ransohoff 85 conducted a systematic review on the CRC risk of individuals with a positive FH for adenomas and finally selected only 2 relevant studies. They concluded that there is an increased risk for CRC, however, those 2 studies harbored limitations regarding generalizability and validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not address the presence of having a FH of adenomas despite current surveillance recommendations according to different clinical practice guidelines. [5][6][7] Imperiale and Ransohoff 85 conducted a systematic review on the CRC risk of individuals with a positive FH for adenomas and finally selected only 2 relevant studies. They concluded that there is an increased risk for CRC, however, those 2 studies harbored limitations regarding generalizability and validity.…”
Section: Discussionmentioning
confidence: 99%
“…According to various clinical practice guidelines, individuals with FCC are recommended to undergo more intensive surveillance strategies than the general population, starting at an earlier age. [5][6][7][8] However, the definition of who should undergo intensified colonoscopy surveillance instead of average-risk screening varies widely.…”
mentioning
confidence: 99%
“…Colonoscopy should be mandatory in older patients and when there is a personal and/or a family history of colorectal neoplasms or documented advanced adenoma, IBD, history of altered bowel habits, recent significant weight loss, and a laboratory findings of iron deficiency anemia or a positive fecal immunochemical test (FIT) and guaiac-based fecal occult blood test (gFOBT) [25][26][27][28][29][30].…”
Section: Patients With Hd and Rectal Bleeding Should Undergo Colonoscmentioning
confidence: 99%
“…63 Guidelines recently published by the Canadian Association of Gastroenterology and endorsed by the American Gastroenterological Association also support starting screening in high-risk individuals at age 40, with a surveillance interval of 5 to 10 years based on the number of first-degree relatives with colorectal cancer or adenomas. 64 Consensus statements were based on retrospective cohort, prospective case-controlled, and cross-sectional stud-ies comparing the risk of colorectal cancer in individuals with a family history against those without a family history.…”
Section: Colonoscopymentioning
confidence: 99%